Human Resource Planning at Baitul Maal Wat Tamwil - Rahmawati, Novita Dina; Cahyani, Rofi'athul Dwi (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2024)
Human resource planning is the process of analyzing and identifying needs and availability to achieve goals. In Human Resource planning there are 2 components, namely needs and availability. Need is determining the number, skills, and location of employees who will be needed in the future to achieve organizational or company goals, while availability is determining whether the company will be safe if it is controlled by employees with the required expertise. Human Resource Planning in general is systematic planning to estimate employee needs and the availability of human resources in the future both in terms of quantity, type and quality to achieve common goals. The objectives of human resource planning are organizational, functional, social, personal goals. Actions that minimize the negative impact on the organization. If an organization fails to use its resources to generate societal benefits it can create obstacles. Personal goals designed to help employees achieve their goals, Minimum goals that increase individual contribution towards the organization, while the personal goals of employees should be consider whether employees should be retained, retired, or motivated. If personal goals are not accomplished, the employee's performance and happiness may suffer and they may quit the business.